Cover Feature: Construction of Biaryl Scaffolds from Iodoarenes and C−H Heteroarenes Using an Amide Base Generated in situ from Aminosilane and Fluoride Anion (Asian J. Org. Chem. 10/2018). Issue 10 (16th October 2018) - Shigeno, Masanori; Kai, Yusuke; Yamada, Tetsuya; Hayashi, Kazutoshi; Nozawa‐Kumada, Kanako; Denneval, Charline; Kondo, Yoshinori
Abstract : The cover image shows that an in situ generated amide base mediates the coupling reaction of iodoarenes and C−H heteroarenes to form a biaryl. This reaction can proceed with electron‐rich, ‐deficient, and ortho ‐substituted haloarenes as well as electron‐rich and ‐deficient C−H heteroarenes. Involvement of a radical intermediate was confirmed by radical‐inhibition experiments, deuterium‐labeling experiments, and EPR spectral measurements. Enhancement of the reactivity of electron‐rich N ‐methylpyrrole was observed in the presence of electron‐poor phenazine or pyrazine. More information can be found in the Full Paper by Masanori Shigeno, Yoshinori Kondo et al. on page 2082 in Issue 10, 2018 (DOI: 10.1002/ajoc.201800438 ).